Religious Moderation in the Dynamics of Mazhaab Differences: A Literature Study in Islamic Education - Ulfa Dwi Lestari; Khawa Isthoifiatal Mufidah; Dievan Alfiralza Supriyanto; Khairul Anam; Siyono (Konsultan Jurnal Ilmiah Indonesia, 2025)
The phenomenon of mazhaab differences among Muslims still faces various problems, such as discrimination and responses to diversity in the form of exclusive behavior among some Muslims. Research by the Setara Institute in 2023 shows that the level of intolerance among students is still high: 0.6% are exposed to violent extremist ideology, 5.0% are actively intolerant, and 24.2% are passively intolerant. This study discusses how religious moderation can be used as a framework and pedagogical approach to address sectarian differences in Islamic education. This study uses a literature review with a descriptive qualitative approach. Data analysis was conducted using an inductive approach, which draws conclusions based on an examination of various literature without using numbers or statistics, as is characteristic of qualitative research that emphasizes meaning and context. The results of the study show that religious moderation in Islamic education is an approach that emphasizes balance, tolerance, and social harmony amid diversity. Islamic education that adopts a multi-sectarian perspective and instills values of moderation can contribute to preventing radicalism, reducing excessive fanaticism, and strengthening social cohesion in the school environment. Religious Moderation, Mazhaab, Islamic Education.